Cover Jurnal Media Teknik Sipil Vol. 10, No.2. Agustus 2012 - Jurnal Media Teknik Sipil, Cover (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2012)
Cover Jurnal Media Teknik Sipil Vol. 10, No.2. Agustus 2012